Knowledge, attitude and practice of pregnant women attending a health facility regarding the COVID -19 pandemic: pre and post-vaccination (Nepal Medical College Journal, 2023)
The world witnessed the introduction of the COVID -19 virus in December 2019. This caused a pandemic for the next two to three years causing 7,67,984,989 deaths worldwide. A hospital based cross sectional descriptive study conducted in the Obstetrics and Gynecology department of Nepal Medical College Teaching Hospital, which is located in a suburban area of Kathmandu. The objective of the study was to assess the knowledge, attitude and practice of the pregnant women regarding the COVID pandemic pre and post-vaccination and its correlation with socio-demographic factors like age and educational level. A total of 418 women participated in the study. In each phase there were 209 women. In the pre-vaccination phase, 8.1% women had good knowledge, 37.8% had positive attitude, and 37.3% good practice. In the post-vaccination phase, 44.5% had good knowledge, 65.5% had positive attitude, and 84.7% had good practices.